2022
DOI: 10.1038/s41598-022-10019-z
|View full text |Cite
|
Sign up to set email alerts
|

Pet ownership and psychological well-being during the COVID-19 pandemic

Abstract: The question of pet ownership contributing to human well-being has received mixed empirical evidence. This contrasts with the lay intuition that pet ownership contributes positively to wellness. In a large representative sample, we investigate the differences that may exist between pet vs. non-pet owners in terms of their well-being during the COVID-19 pandemic, and examine among different sociodemographic strata, for whom pet ownership can be more vs. less beneficial. A cross-sectional questionnaire survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…In Australia, where unowned 'feral' cats are killed as part of environmental pest management across the country (urban, rural, and remote areas [98]), an estimated 316,000 cats were killed in 2017-2018 [90]. Yet an estimated 60% of people in Australia own a pet cat [99] and are managed under companion animal ownership legislation and policy [98].…”
Section: Coexistence Between Humans and Domestic Cats In The Anthropo...mentioning
confidence: 99%
“…In Australia, where unowned 'feral' cats are killed as part of environmental pest management across the country (urban, rural, and remote areas [98]), an estimated 316,000 cats were killed in 2017-2018 [90]. Yet an estimated 60% of people in Australia own a pet cat [99] and are managed under companion animal ownership legislation and policy [98].…”
Section: Coexistence Between Humans and Domestic Cats In The Anthropo...mentioning
confidence: 99%
“…Aminot et al showed us that dog owners reported higher vitality and life satisfaction and lower loneliness and COVID-related impacts [12]. In our study 44.95% of dog owners actively involved in its care were worried about potential oral health problems during pandemic restrictions, a lower percentage compared with 52.05% of the general population.…”
Section: Discussionmentioning
confidence: 41%
“…In this context, studies suggest that animal companionship might be associated with increased symptoms of depression, higher levels of emotional distress, and a lower quality of life, especially during crises [ 15 , 16 , 17 ]. Moreover, the results indicate that, for example, during specific stressful situations such as the COVID-19 pandemic, pet owners report lower vitality, lower life satisfaction, and a lower life meaning, which might lead to the assumption that pets may contribute to an increased burden among owners [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the COVID-19 pandemic provided an opportunity for researchers in this field to examine this phenomenon with regard to a global stressor, affecting individuals worldwide, in more detail. In this context, most of the studies indicate a significant and complex influence of animal companionship and related responsibilities in the context of stress experience that seems to be strongly determined by external stressors [ 15 , 17 , 18 ]. Therefore, the present study aimed to investigate a wide range of external stressors that animal caregivers were exposed to during the last two years of the pandemic, including the long-term effects of a COVID-19 infection (“Long-Covid” or “Post COVID-19 condition”) [ 22 ] and concerns related to caring for an animal as well as the pandemic itself.…”
Section: Introductionmentioning
confidence: 99%